Role of Trypanosoma cruzi Trans-sialidase on the Escape from Host Immune Surveillance - Nardy, Ana F. F. R.; Freire-de-Lima, Celio G.; Pérez, Ana R.; Morrot, Alexandre (Frontiers in Microbiology, 2016)
Chagas disease is caused by the flagellate protozoan Trypanosoma cruzi, affecting millions of people throughout Latin America. The parasite dampens host immune response causing modifications in diverse lymphoid compartments, including the thymus. T. cruzi trans-sialidase (TS) seems to play a fundamental role in such immunopathological events. This unusual enzyme catalysed the transference of sialic acid molecules from host glycoconjugates to acceptor molecules placed on the parasite surface. TS activity mediates several biological effects leading to the subversion of the host immune system, favouring both parasite survival and the establishment of chronic infection. This review summarizes current findings on the role of TS on the immune response during T. cruzi infection.